Membentuk Parenting Educator untuk Mengatasi Tantrum pada Anak Prasekolah - Izzatul Fithriyah; Zulfa Zahra; Yunias Setiawati (Universitas Mathla'ul Anwar Banten, 2021)
ESTABLISHING PARENTING EDUCATOR TO OVERCOME TANTRUM IN PRESCHOOL CHILDREN. Tantrums or temper tantrums are a condition of the child's anger and emotions expression because the child's intentions and goals are difficult to convey. The cause of tantrums is closely related to family conditions. Early identification of abnormal tantrum behaviors and parenting interventions directed at helping parents deal with tantrums can prevent adverse long-term consequences. Methods: Parenting training and workshops to overcome tantrums to parents and teachers of kindergarten and play group in Gugus V, Kecamatan Kertosono. Result: parenting training and workshop was attended by 40 parents and teachers of kindergarten and play group in Gugus V, Kecamatan Kertosono. The level of participants' knowledge of tantrums are varied. Subjectively, 37.83% of participants stated that they understood tantrums and 62.16% stated that they did not understand about tantrums. After parenting training and workshops to overcome tantrums done, the results are increasing in knowledge about tantrum from 6.05 to 7.48. Conclusion: Parenting training and workshops to overcome tantrums in preschool children as a form of mental health education provide benefits of knowledge to teachers and parents of kindergarten and play group in Gugus V, Kecamatan Kertosono.